Seguridad laboral y riesgos mecánicos en los trabajadores de los talleres de Automekano CÍA. LTDA. Propuesta de un manual de prevención para los trabajadores de la empresa. - Tapia Terán, Hugo Alejandro (2012)
The fundamental objective is to evaluate the application of the Occupational Safety and Mechanical Risk regulations in the company's workshops; and, propose a manual of procedures for the prevention of risks of the workers of the company Automekano Cía. Ltda., in order to disseminate occupational health and safety regulations. The problem identified is the lack of knowledge of workers about safety regulations and occupational risk prevention since this affects the accident rate of the company Automekano Cía. Ltd.; and, the proposal of a prevention manual is proposed to improve the working conditions of the company's workers.